The Effect of Work Discipline and Work Environment on Employee Performance at PT. Pancaran Karya Citra Jakarta - Widhi Wicaksono; Umi Narimawati; Azhar Affandi; Sidik Priadana; Heri Erlangga (International Journal of Education, Information Technology, and Others, 2022)
The purpose of this study was to determine the effect of partially or simultaneously between Work Discipline and Work Environment on Employee Performance at PT. Pancaran Karya Citra Jakarta. This research method is associative research with a quantitative approach. The results showed that, Work Discipline (X1) Affects Employee Performance (Y) At PT. Pancaran Karya Citra Jakarta, with a tcount value of 8.806 > ttable 1.988 or a Sig value of 0.000 < 0.05, then Ho1 is rejected and Ha1 is accepted. Work Discipline (X1) is Strongly Related to Employee Performance (Y) At PT. Pancaran Karya Citra Jakarta. The ability of the Work Discipline variable (X1) in explaining the Employee Performance variable (Y) at PT. Pancaran Karya Citra Jakarta is 47.1% and the remaining 52.9% is influenced by other factors. Work Environment (X2) Affects Employee Performance (Y) At PT. Pancaran Karya Citra Jakarta, with a tcount value of 13,564 > ttable 1,988 or a Sig value of 0.000 < 0.05, then Ho2 is rejected and Ha2 is accepted. Work Environment (X2) has a very strong relationship with employee performance (Y) at PT. Pancaran Karya Citra Jakarta. The ability of the Work Environment variable (X2) in explaining the Employee Performance variable (Y) at PT. Pancaran Karya Citra Jakarta amounted to 67.9% and the remaining 32.1% was influenced by other factors. Work Discipline (X1) and Work Environment (X2) Simultaneously Affect Employee Performance (Y) At PT. Pancaran Karya Citra Jakarta, with a value of Fcount 91.559 > Ftable 3.103 or a Sig value of 0.000 <0.05, then Ho3 is rejected and Ha3 is accepted. The regression equation Y = 22.592 + 0.062x1 + 0.450x2. This regression equation can be concluded that, Work Discipline (X1) and Work Environment (X2) Have a Positive Influence Direction on Employee Performance (Y) At PT. Pancaran Karya Citra Jakarta. Work Discipline (X1) and Work Environment (X2) are very strongly related to employee performance (Y) at PT. Pancaran Karya Citra Jakarta. The ability of the Work Discipline (X1) and Work Environment (X2) variables in explaining the Employee Performance variable (Y) at PT. Pancaran Karya Citra Jakarta amounted to 68% and the remaining 32% was influenced by other factors.